Workplace ostracism through the lens of reciprocity theory / Farsha Farahana Ahmad Izhan, Nor Azairiah Fatimah Othman and Muhammad Majid - Ahmad Izhan, Farsha Farahana; Othman, Nor Azairiah Fatimah; Majid, Muhammad (UiTM Cawangan Johor, 2024)
Establishing a healthy co-worker relationship is the heart of developing a harmonious working environment. The area of organizational behaviour has paid less attention to workplace ostracism (WO) which can have a negative impact on the workplace environment. It is a prominent issue in the workplace that needs to be further investigated and studies on this issue are diverse and large. Thus, this paper comprehensively reviews the literature related to WO in two aspects. Firstly, it discusses counterproductive work behaviour (CWB) as an implication of ostracism from the perspective of reciprocity theory. Secondly, to investigate emotional intelligence (EI) potential to mitigate ostracized employees from acting defensively at work. This paper reveals that CWB emerged as a toxic behaviour due to WO. Meanwhile, positive EI can prevent employees from ostracizing others. Addressing this issue can reveal that CWB can potentially lead to ostracizing behaviour and EI as a reducing factor to the relationship.